2017
DOI: 10.1080/21541264.2017.1322668
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor and miR-206 regulation in prostate cancer

Abstract: In the United States, prostate cancer is the second leading cause of cancer-related deaths among men with an approximately 220,000 patients diagnosed with the disease in 2015. Prostate cancer is a hormone-driven tumor, and a common therapy is androgen-deprivation therapy (ADT) that involves anti-androgen treatments and/or castration therapy. Understanding the molecular basis for androgen-independent tumors is crucial toward developing new therapies for these patients. Understanding how androgen receptor itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…Several miRNAs, which can serve prognostic roles, have been reported to be associated with PCa. A recent study presented that miR-206 binds with the androgen receptor and regulate the hormones in both breast and prostate cancer [ 29 ]. While miR-186-5p was found to play an oncogenic role in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs, which can serve prognostic roles, have been reported to be associated with PCa. A recent study presented that miR-206 binds with the androgen receptor and regulate the hormones in both breast and prostate cancer [ 29 ]. While miR-186-5p was found to play an oncogenic role in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we reported sex-specific differences of peripheral miRNA levels in some NDs. As an example, miR-206, which is underexpressed in males with FTD and overexpressed in males with ALS, is regulated by hormones [ 94 , 95 , 96 ]. MiR-132 was found to be a particularly expressed miRNA in the cerebellum of males [ 97 ], which might explain why Yang and co-authors found it to be more upregulated in plasma samples of male patients with PD.…”
Section: Conclusion and Futures Perspectivesmentioning
confidence: 99%
“…28 All these studies further suggest that miR-206 may act as a tumor suppressor in multiple cancers. Although multiple studies of the function of miR-206 in PCa have been described, [29][30][31] the molecular mechanisms related to miR-206, however, remain obscure but attractive.…”
mentioning
confidence: 99%